New dextrin nanomagnetogels as contrast agents for magnetic resonance imaging - Gonçalves, C. (2013)
This study aims at the production and characterization of a “nanomagnetogel” consisting of superparamagnetic iron oxide nanoparticles (g-Fe2O3) stabilized within a hydrophobized-dextrin nanogel. The nanomagnetogel obtained was extensively characterized with respect to physico-chemical (transmission electron microscopy, cryo-scanning electron microscopy, dynamic light scattering, small angle X-ray scattering), magnetic (relaxometry, MIAplex) and biocompatibility (interaction with cells) properties. The obtained nanomagnetogel formulation, with about 4 mM of iron and a diameter of 100 nm, presents relevant features as a promising magnetic resonance imaging (MRI) contrast agent, noteworthy superparamagnetic behavior, high stability, narrow size distribution and potential for magnetic guidance to target areas by means of an external magnetic field. High values of transverse relaxivity make the nanomagnetogel a promising T2 contrast agent, allowing enhanced lesion detectability through magnetic resonance imaging. The nanomagnetogel demonstrated non-toxicity for 3T3 fibroblast cultures and was efficiently internalized by bone marrow-derived macrophages, therefore having potential as a contrast agent for MRI of the organs associated with the reticuloendothelial system (spleen, liver). The production of the nanomagnetogel is simple and easy to scale up, thus offering great technological potential.